MIMICRY AND AMBIVALENCE AS MANIFESTED IN BEND IT LIKE BECKHAM MOVIE - AFANDI, AFIF (Jurnal Ilmiah Mahasiswa FIB, 2014)
Keywords: postcolonialism, mimicry, ambivalency    British colonialism in India made the Indian society struggle to reach their independence. After had got independence on August 15, 1947 many Indian people did migration to Britain. The effect of Indians migration to British country has created technical term of India diaspora. Diaspora in Britain made British identity become heterogeneous in homogeneous in the reality and cinema. Diaspora also has created the problems of multiculturalism, hibridity, mimicry and ambivalence. This research is about the searching for manifestation of mimicry and ambivalence which is manifested in Bend It Like Beckham movie as the movie that tells about the problem of diaspora.This study uses a qualitative research employing two concepts, namely mimicry and ambivalence with postcolonialism approach. The analysis is based on the literal facts found in Bend It Like Beckham movie and supported by those concepts.The results show that in Bend It Like Beckham movie there are manifestations of mimicry and ambivalence. Mimicry happens in the cultural aspects of society that is manifested in language, games, fashion, cuisine, and lifestyle. Mimicry also happens in the cultural aspects of art that can be seen in fashion. While The manifestations of ambivalence happen in cultural aspects of society such as in language, cuisine, game and lifestyle.By using the same material object, the writer suggests to the next researcher to use Feminism, because Bend It Like Beckham also talks about the struggle of women to reach her dream as a woman football player.